Three-, four- and five-day microcycles in professional football - Gualtieri, A.; Vicens-Bordas, J.; Rampinini, E.; Ferrari Bravo, D.; Beato, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: In modern football, elite level teams frequently face periods with congested fixtures. This scenario requires teams to play more than once a week in national and international competitions [1]. Previous research reported a gradual reduction in training volume as match day approached [2], but limited information is currently available about shorter microcycles` training load distribution. Therefore, this study aimed to quantify training and match day (MD) load during three- (3dMC), four- (4dMC) and five-day microcycles (5dMC) in elite adult football and analyse the effect of microcycle length on the training load sustained the day before (MD-1) and after a match (MD+1). METHODS: This study involved 20 male adult elite football players whose external load was monitored for a whole competitive season, assessing periods with congested fixtures (i.e., three-, four- and five-day microcycles). Training exposure (EXP), total distance covered (TD), high-speed running distance (HSR), sprint distance (SD), individual sprint distance (D>80%), number of accelerations (ACC) and decelerations (DEC) were quantified. The load recorded on MD+1 (sustained by non-starting players), MD-1 and MD was compared between the three congested microcycles. RESULTS: Microcycles length affected most of the variables of interest: HSR (F = 9.04, p < 0.01), SD (F = 13.90, p < 0.01), D>80% (F = 20.25, p < 0.01), accelerations (F = 10.12, p < 0.01) and decelerations (F = 6.01, p < 0.01). Comparisons highlighted that 3dMC and 4dMC had greater daily average HSR and D>80% demands than the 5dMC, while 4dMC and 5dMC produced more ACC than 3dMC (p < 0.05). There was an interaction effect between training day and microcycle type for SD (F = 5.46, p < 0.01), D>80% (F = 4.51, p < 0.01), ACC (F = 2.24, p = 0.06) and DEC (F = 3.91, p < 0.01). In particular, the microcycle type affected D>80% on MD+1 (higher in 3dMC), and ACC and DEC on MD-1 and MD. 4dMC presented a greater number of ACC on MD-1, compared to 3dMC (-8.5, p < 0.01, d = -0.29) and on MD compared to 3dMC (-11.6, p < 0.01, d = -0.36) and 5dMC (-9.3, p < 0.01, d = 0.25). 4dMC presented the greater number of DEC on MD-1, compared to 3dMC (-7.9, p < 0.01, d = -0.23) and on MD compared to 3dMC (-16.4, p < 0.01, d = -0.43) and 5dMC (14.2, p < 0.01, d = 0.33). CONCLUSION: During congested fixtures, players external training load is influenced by microcycles length, where coaches seem to prefer technical and tactical drills with a reduced muscular impact during shorter microcycles allowing starting players to recover from the previous match. On the other side, non-starting players can be exposed to high-speed running on MD+1 since they may not have this stimulus on the other training days of the week. Independently of the length of the congested fixture microcycle, daily load does appear to decrease when MD approaches.